Comparing the Efficacy of Platelet-Rich Fibrin (PRF) With the Buccal Advancement Flap for the Closure of Acute Oroantral Communication - Awal, Dr. M. A.; Akhter, Dr. Mahmuda (International Journal of Innovative Research in Medical Science, 2020)
Oroantral communication (OAC) is a pathological communication between the oral cavity and the maxillary sinus. Numerous methods are described to manage an acute OAC with some adverse effect and limitations. Our comparative cross-sectional study tried to evaluate the efficacy of Platelet-rich fibrin (PRF) by comparing with the Buccal advancement flap for the closure of acute OAC on 38 patients (n=38), were divided into two groups. One group treated by traditional Buccal advancement flap and compared with the group treated with PRF clot and membranes. Statistically significant better healing with less complication was observed (P< 0.05) in group treated with PRF clot and membranes considering as an effective way to manage acute oroantral communications.